Firm structure and the location decision of German manufacturing firms: Evidence from official firm-level data - Astrid Krenz (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2016)
This paper uses a comprehensive, official firm-level dataset for German manufacturing firms to investigate the location decision of new firm activity in the German regional economy, differentiated by firm structure. The rich regional dimension of this dataset is investigated for the first time in regard to the location choices of firms. Results reveal that agglomeration economies play a significant role for small firms, but not for medium-sized and large firms. Whereas the market potential exerts a significant positive impact for all firms, labor costs do not exert a significant impact on large firms' location decisions.
Keywords: R11; R12; 330; Firm location; Regional economy; Agglomeration economies